Enviroeconomic optimization of insulation thickness for building exterior walls through thermoeconomic and life cycle assessment analysis - Mehmet Kadri Akyüz (Case Studies in Thermal Engineering)
The economic optimum insulation thicknesses (OIT) for heated buildings in five different climate regions in Turkiye were determined, and the energy, cost, and life cycle-based environmental performances were analyzed. Calculations were performed using three different fuels (natural gas, fuel oil, and coal) and four different insulation materials: expanded polystyrene (EPS), rock wool (RW), glass wool (GW), and extruded polystyrene (XPS). This study utilized a thermoeconomic approach to evaluate energy and economic performance and a life cycle assessment (LCA) approach to assess environmental impacts, ensuring a comprehensive analysis of insulation strategies. The impacts of climate change factors were expressed as kg CO2 equivalent (kgCO2eq) using 100-years global warming potential (GWP). The annual energy savings varying from 18.41 to 258.15 kWh/(year.m2) for the warmer and the colder climate zones, respectively. The maximum avoided environmental impact (AEI) due to energy saved from thermal insulation was 144.11 kgCO2eq/(year.m2) for coal and RW in coldest climate zone, while the minimum AEI was 5.31 kgCO2eq/(year.m2) for natural gas and XPS in warmest climate zone. Among insulation materials, EPS offers the shortest environmental payback period, whereas RW requires the longest, highlighting material-specific trade-offs. In all climate zones, environmental payback periods are much shorter than economic ones.